Application of The Concept “Ngugemi Ajaran Leluhur” To Prevent Mon-ey Politics in Sedulur Sikep Community in Pati, Central Java - Sri Wahyu Ananingsih; Sukirno Sukirno; Agung Basuki Prasetyo; Faishal Hafizha A (Eduvest - Journal of Universal Studies, 2024)
The practice of money politics is one type of electoral and regional election crime. In practice, not all money politics cases can proceed to the Courts. For example,based on data from the Bawaslu of Central Java Province, the number of alleged money politics in the 2019 election was 66 cases. Of the 66 cases that can be processed to court, only 5 cases. This can be stated that so far law enforcement against cases of money political practices in elections has not been optimal. Therefore, repressive and preventive efforts are needed. One of the preventive efforts as carried out by the Sedulur Sikep community living in Baturejo Village, Sukolilo District, Pati Regency. This community applies the concept of "ngugemi ajaran leluhur" which contains ancestral principles and teachings to reject money politics. This study is interesting because currently the values of local wisdom are starting to fade but the people of Sedulur Sikep are still implementing and maintaining the values of local wisdom. The urgency of this research is as a reference or input for the government or related institutions in the context of conceptualizing the prevention of money politics in elections. The results of this study concluded that the concept of "ngugemi ajaran leluhur" containing ancestral principles and teachings is still applied and used as a guideline for life by the Sedulur Sikep community until now. The Sedulur Sikep community's rejection of money politics in elections is based on its adherence to ancestral principles and teachings.